Assessment of prevalence and risk factors for anaemia in pregnant women attending Karnataka institute of medical sciences, outpatient department, Hubballi, Karnataka, India - Bant, Dattatraya D.; Kumar, Shiv (International Journal Of Community Medicine And Public Health, 2020)
Background: Anaemia in pregnancy is one of the major causes of maternal morbidity and mortality in India and world. Anaemia in pregnancy continues to be a problem in spite of national programs for its prevention and control. It accounts for 1/5th of maternal deaths worldwide and 16% in India and is the major factor responsible for low birth weight, abortions, premature birth, and post-partum haemorrhage. Hence determining the status and factors influencing anaemia among pregnant women is essential to treat and prevent the same. Objective of this study was to assess the prevalence and risk factors associated with anaemia among pregnant women. Methods: A cross sectional study was conducted among 200 pregnant women attending for antenatal care at KIMS OPD from 3rd June to 4th July. A pretested, semi-structured questionnaire was applied to collect data. Haemoglobin estimation was done by Sahli’s method. Results: Prevalence of anaemia among pregnant women was found to be 81%; majority had moderate anaemia 57%. The mean age of pregnant women in the study is 24.55 years and 46.5% belong to lower socioeconomic status, 43% lived in joint families. Factors influencing anaemia were multi-parity, short inter-pregnancy interval, no history of recent deworming and iron and folic acid tablets intake. Conclusions: In the present study, the prevalence of anaemia among pregnant women was found to be very high i.e., 81% especially among illiterates, low income groups, multiparous women, short inter-pregnancy interval, no history of recent deworming and iron and folic acid tablets intake.